Applying Realia for Teaching Writing Skill at First Grade Students of Papua Senior High School - Isnaini Eddy Saputro (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Realia is a kind of media that can be used by the teachers to increase students’ skill in writing descriptive text for stimulating the students’ idea. This research is aimed to to increase the students’ writing skill at Papua senior high school. The sample of this research is 20 students of first grade at SMA Negeri 3 Sorong. The researcher uses quantitative method of one group pre-test and post –test as pre-experimental design. To collect the data of applying realia for teaching writing, it is used writing test that divided into pre-test and post test. Those tests are aimed to evaluate the applying of realia for students who learning English in writing skill. The kind of writing test is showed by descriptive text and analysed by using the effectiveness of treatment score that determined by mean score of pre-test and post test. The finding shows that the researcher found students’ difficulties in writing skill from the pre-test result. Their obstacles in writing skill covered organizing the words, vocabulary, and grammar. The researcher applied relia to drill the students how to describe the realia by following the steps of descriptive text. The researcher concluded the result of pre – test and post test have different score. It showed by the pre –test (T1) was 58.75 and post test (T2) 65.62. It means that the students’ writing skill is better when they learn English by writing an descriptive text using realia.